The effects of structural and electrical properties of hollow fiber nanofiltration membranes on salt and dye removal under different solution properties - Ismail, Ahmad Fauzi; Lau, Woei Jye (Penerbit UTM Press, 2008)
Three different characteristics of self-made hollow fiber nanofiltration (NF) membranes with different structural and electrical properties were evaluated for their suitability for removing salt and colour under different solution properties. Results showed NF achieved promising dye retention for the reactive dyes used at different concentrations and varied slightly with pH. The retention of salt was found to be dependent on solution properties and membrane electrical properties where higher retentions were achieved under alkaline condition and by using NF membrane with higher surface charge value. The greater membrane negative surface charge properties has also made the membrane less fouling-sensitive to dye absorption and improving the economic viability of the treatment process.